Pelatihan Ms. Power Point untuk Melatih Keterampilan Pengurus Daerah Aisyiyah Se Kabupaten Gresik - Rakhma Devi, Putri Aisyiyah; Soffiana Agustin (Jurnal Pengabdian Masyarakat dan Lingkungan (JPML), 2025)
The Microsoft PowerPoint presentation program for Aisyiyah members in Gresik Regency aims to improve digital literacy among women in Islamic community organizations. Through this training, participants will learn the basics of using PowerPoint, such as creating slides, inserting media, and using animations. The training format includes demonstrations, Q&A sessions, and practical exercises. The results of the activity showed that participants were highly motivated and able to apply the skills they learned to organizational activities. The training not only improved the technical skills of the women but also enabled them to carry out their organizational tasks more actively and professionally. This initiative is a strategic step to encourage the digitalization of organizations and strengthen the role of women in modern society.